Have state renewable portfolio standards really worked? Synthesizing past policy assessments to build an integrated econometric analysis of RPS effectiveness in the US - Gireesh Shrimali; Steffen Jenner; Felix Groba; Gabriel Chan; Joe Indvik (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Renewable portfolio standards (RPS) are the most popular U.S. state-level policies for promoting deployment of renewable electricity (RES-E). While several econometric studies have estimated the effect of RPS on in-state RES-E deployment, results are contradictory. We reconcile these studies and move toward a definitive answer to the question of RPS effectiveness. We conduct an analysis using time series cross sectional regressions - including the most nuanced controls for policy design features to date - and nonparametric matching analysis. We find that higher RPS stringency does not necessarily drive more RES-E deployment. We examine several RPS design features and market characteristics (including REC unbundling, RPS in neighboring states, out-of-state renewable energy purchases) that may explain the gap between effective and ineffective policies. We also investigate other RES-E policies and technology-specific effects. Ultimately, we show that RPS effectiveness is largely explained by a combination of policy design, market context, and inter-state trading effects.
Keywords: C23; H23; Q42; Q48; 330; Renewable energy; Renewable portfolio standards; Panel data models; Matching analysis